The Effect of Layer Thickness on Stress Ratio and Fatigue Service Life of Plain Concrete Slab Track Structure - Pasadena, Emeralda Insani Nuansa Singgasana Pelangi Jelita Dialiran Sungai; Barasa, Willy; Prabawa, Hanafi Isnanta; Fiantika, Thiya; Aspar, Wimpie Agoeng Noegroho; Primadiyanti, Suci Putri; Waseso, A B; Piscesa, Bambang; Purnomo, Dwi Agus (International Journal of Integrated Engineering, 2023)
Indonesia has been developing a high-speed railway. Therefore, it is necessary to study slab track design configuration, which is convenient and efficient, by considering the country’s environmental, geological, and geographical conditions. This paper discusses the effect of the layer thickness on the stress ratio and fatigue service life of slab track layers. The Finite Element Method (FEM) analysis was performed to numerically simulate the maximum moment caused by 180 kN of axle load. Subsequently, the classic calculation of stress ratio and fatigue service life was conducted for various layer thicknesses. The same materials specifications, axle load, and the value of subgrade reaction were applied for all slab track configurations with various thicknesses. The results indicate that the thicker each layer is, the lower stress ratio and the higher fatigue service life. The thicknesses influence the contribution of each layer in resisting the axle load in the slab track system. The slab track design is still conservative because friction between each layer of the slab track design configuration was not considered. The analysis was conducted for plain concrete slab without any reinforcement. The results are interesting for practicing engineers and researchers, and more case studies might be beneficial.